Étude différentielle et évolutive des valeurs de travail dans le contexte d’une vérification de la théorie de Holland - Aubin, Stéphan (Canadian Journal of Counselling and Psychotherapy, 2011)
This study deals with the evolution and the differentiation of work values in relation with Holland's personality typology. High school (N = 1247), college (N = 1433), and university (N = 1929) students completed the Questionnaire de Valeurs de Travail (Perron & Dupont, 1974) and were also classified in terms of personality types on the basis of their expressed preference for an occupation. Results obtained from a 3 x 6 MANOVA show an interaction between levels of education and personality types. Further, discriminant analyses indicate that differentiation of work values according to personality types systematically increases from high school to university